2004
DOI: 10.1074/jbc.m314191200
|View full text |Cite
|
Sign up to set email alerts
|

Double Strand Break Repair by Homologous Recombination Is Regulated by Cell Cycle-independent Signaling via ATM in Human Glioma Cells

Abstract: To investigate double strand break (DSB) repair and signaling in human glioma cells, we stably transfected human U87 (ATM ؉ , p53 ؉ ) glioma cells with a plasmid having a single I-SceI site within an inactive green fluorescent protein (GFP) expression cassette, allowing for the detection of homologous recombination repair (HRR) by GFP expression. HRR and nonhomologous end joining (NHEJ) were also determined by PCR. DSB repair was first detected at 12 h postinfection with an adenovirus expressing I-SceI with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 66 publications
9
98
0
2
Order By: Relevance
“…Mouse models recapitulate many of the phenotypes seen in patients with ATM mutations, including tumor predisposition, radiosensitivity, and gonadal dysgenesis (30,33,34). Although some studies using transformed cell lines have reported that ATM is not required for HDR (44), others have suggested that ATM plays a critical role (45,46). ATM has been reported to be necessary for DSB resection to generate Replication protein A (RPA)-coated ssDNA (29), an essential early intermediate in HDR.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models recapitulate many of the phenotypes seen in patients with ATM mutations, including tumor predisposition, radiosensitivity, and gonadal dysgenesis (30,33,34). Although some studies using transformed cell lines have reported that ATM is not required for HDR (44), others have suggested that ATM plays a critical role (45,46). ATM has been reported to be necessary for DSB resection to generate Replication protein A (RPA)-coated ssDNA (29), an essential early intermediate in HDR.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we and others showed that IR-induced checkpoint response mainly promotes HRR and has little effect on NHEJ. [7][8][9][10] These results provide important information that because the NHEJ pathway is inhibited in high LET irradiated cells, HRR might play a more protective role in such cells than that in low LET irradiated cells; because checkpoint facilitates mainly the HRR pathway, checkpoint response might be a more efficient factor for modifying cell sensitivity to high LET IR than to low LET IR. To test this hypothesis, we examined and analyzed the RBE on sensitivity in ATM or ATR, the two most important checkpoint genes, deficient or kinase dead cell lines following either high LET or low LET IR.…”
mentioning
confidence: 89%
“…This response differs from ATM, another important checkpoint protein that mainly responds to IR but not to UV-induced DNA damage. The role of ATM in cellular radiosensitivity is linked to HRR (11,12), but which pathway, HRR or NHEJ or both, is responsible for the effects of ATR on the sensitivity of cells to IR remains unclear. Our results previously suggested that DNA damage-induced checkpoint facilitates HRR but not NHEJ (7,8).…”
Section: Introductionmentioning
confidence: 99%